Hidden ekphrasis in the works of Miroslav Krleža - Šegota Lah, Nataša (Ars et humanitas, 2017)
Throughout the entire literary oeuvre of Miroslav Krleža we are faced with a great number of credible descriptions, describing real historic events, or real artists and artworks belonging to the rich resources of European art history. By applying a cryptographic method of incorporating descriptions into his texts, Krleža on the one hand hid his sources, while on the other also revealed them. He hid them in the tissue of fictional texts, and unmasked them using a key work only those familiar with the source could identify. We term this method the use of "belletristic cryptograms", and can further categorise it into thematic subgroups of concealed artwork descriptions, naming this whole method the use of hidden ekphrasis. The choice of artworks Krleža describes in his work is comprehensive, diverse and each described differently. Since we are dealing with literary texts, descriptions are often used in the function of a wide array of interpretative strategies of depiction; in some aspects, they are used as a mere glimpse into a piece of art with the goal of visually associating, evoking or minutely symbolizing the incorporeal frame of an artist's mind or of the wider social context. In other aspects, the artworks are richly and meticulously presented with regard to their importance and credibility as they, according to Krleža, possess an "ethical intelligence" and "ethical conscience". Only Krleža's prose is researched here, and this is done on two levels. We take a look at examples where real art is incorporated into fictional texts in order to determine the significance and meaning of a certain dialogue, mise-en-scene or situation. This is most commonly found in the author's plays, novels and novellas. On the other hand, we can trace a completely opposite method by which artworks enter these texts, where, due to their historic determination and already established worth/ status, they thus re-enter reality, as seen from the perspective of Krleža's life and work, so as to yet again test art history's credibility through the matrix of contemporaneity. This approach is most often found in Krleža's essays, critiques and diary entries.
Keywords: ekfraza; hrvaška književnost; Krleža, Miroslav; leposlovni kriptogrami